The Effect of Variations In Clear Coat Application Distance On The Glitter of The Painting Results - Najib Fatkhurokhman; Hanif Hidayat; Haris Nubli (Jurnal Inovasi Mesin, 2025)
Painting defects in  the repainting  process in the vehicle body repair industry are still a common problem. The main factor causing painting defects is manual application that is not in accordance with standard operating procedures. Painting the vehicle body functions to protect the surface and increase aesthetic value, but there are still frequent painting defects such as rough surfaces, spots, and melting due to improper application. This study aims to examine the distance of application of clear coat to the quality of painting results with minimal defects. The research design used was an experimental  research design with a variety of spraying distances of 10 cm, 15 cm, 20 cm, 25 cm and the measurement of the gloss value was carried out using a gloss meter. The results of the study show that the spraying distance greatly affects the gloss value of the painted results. A distance of 15 cm results in the best gloss value of 90.94 GU with no paint defects, while a distance of 25 cm results in the lowest gloss value of 58.50 GU with rough and dull surfaces. Too close a distance increases the shine power but has the potential to cause defects in the form of  a melted clear coat  layer. This study concluded that the optimal distance for spraying clear coats is 15 cm to achieve high-quality painting results